Manajemen Kepala Madrasah dalam Meningkatkan Hasil Belajar Peserta Didik di MTs Ma’arif Al-Hikmah Mekarsari - Badriyah Badriyah; Asep Saepurrohman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
Educational institutions, whether formal, informal, or non-formal, are places for the transfer of knowledge and culture. Schools are one of the educational organizations that can be considered as a means to achieve national educational goals. The success of education in schools depends on the human resources available in those schools, namely the principal, teachers, students, administrative staff, and other educational personnel through educational practices. To improve the quality of education in schools, school principals must be able to utilize any resources available in the school environment through various managerial processes aimed at enhancing educational quality through student learning outcomes, both in terms of the teachers and the achievements of the students. Improving student learning outcomes is an effective solution for enhancing the quality of education. The problem formulation in this thesis is how the school management process carried out by the head of the madrasa improves the learning outcomes of students at MTs Ma'arif Al-Hikmah Mekarsari, Cimerak District, Pangandaran Regency. The research conducted at MTs Ma’arif Al-Hikmah Mekarsari in Cimerak District, Pangandaran Regency, aims to objectively describe how the school management process is carried out by the head of the madrasah at MTs Ma’arif Al-Hikmah Mekarsari in Cimerak District, Pangandaran Regency. The type of research used is field research that is descriptive in nature. The data collection techniques used include interview techniques and documentation techniques. Meanwhile, to analyze the obtained data, the author does so by collecting all the data, reducing the data, presenting the data, and verifying the data. The research results indicate that the school management process carried out by the head of the madrasa at MTs Ma’arif Al-Hikmah Mekarsari, Cimerak District, Pangandaran Regency, is conducted through the processes of planning, organizing, implementation, and evaluation.